A Review Study of Food According to Prakriti and Doshas - Meghwal, Chetan Ram; singh, Vikram; meena, Mamta kumara; Sharma, Ashok Kumar; Sharma, K L; meena, Rekhraj; Nigam, Ayushi (International Research Journal of Ayurveda & Yoga, 2023)
In Ayurveda, food according to Prakriti plays an important role in determining an individual’s ahara, vihar, achara, and parihara; following this leads to a healthy life. Today’s society is conscious and always curious about diet and nutrition; as a result, they blindly follow what they see in the newspaper, on TV, and so on. They think that the particular diet has so many qualities that give them better health. But all the food is not for everyone due to different Prakriti according to Ayurveda and also such type of advertisements are general and especially for marketing. One should know the suitability for particular food towards their body and than after consuming it. Hence knowledge of Prakriti and food for different Prakriti is very essential. This particular subject has been chosen for the current study to evaluate the role of diet and lifestyle in different constitutions (Prakriti) for achieving health as well as in the manifestation of diseases, and after following them to check the changes taking place in health status. So here, food for each Prakriti is given.